Incidence and associated factors of gestational diabetes mellitus diagnosed during 24-28 weeks of gestation - Artitaya Singwongsa; Dittakarn Boriboonhirunsarn (The Royal Thai College of Obstetricians and Gynaecologists, 2016)
Objectives:To determine incidence and associated factors of gestational diabetes (GDM) diagnosed at 24-28 weeks of gestation. Materials and Methods:A total of 200 pregnant women at risk for GDM who attended antenatal clinic before 20 weeks of gestation and had negative GDM screening tests were enrolled. All women received a second screening test at 24-28 weeks of gestation, according to institutional guideline. Data was retrieved, including demographic data, GDM risks and diagnosis, weight gain during pregnancy, and labor and delivery data. Incidence of GDM diagnosed by second screening test was estimated and possible associated factors were identified.Results:Mean maternal age was 31 years, and 51% were nulliparous. Most common GDM risks were age > 30 years (70%) and family history of diabetes (46%). Majority of women had normal pre-pregnancy BMI (63%) and normal weight gain (43.5%), while 38% gained weight greater than recommendation. Incidence of GDM diagnosed at 24-28 weeks of gestation was 15%. Various characteristics were comparable among late-onset GDM and non-GDM group, including age, parity, pre-pregnancy BMI, and gestational weight gain. However, late-onset GDM group had significantly greater second trimester weight gain (7.2 ± 2.8 kg vs. 5.9 ± 2.4 kg, p=0.01). Compared to women with normal GCT, abnormal 50-g GCT and abnormal 1 OGTT value at first screening significantly increased the risk of late-onset GDM (9.5%, 18.2%, and 47.4% respectively, p<0.001).Conclusion: Incidence of GDM diagnosed at 24-28 weeks of gestation was 15%. High second trimester weight gain and abnormal first screening results significantly increased the risk of late diagnosed GDM.